The IceCube Neutrino Observatory Part I: Point Source Searches - Collaboration, I; Aartsen, MG; Abbasi, R; Abdou, Y; Ackermann, M; Adams, J; Aguilar, J; Ahlers, M; Altmann, D; Auffenberg, J; Bai, X; Baker, M; et al. (2013)
Papers on point source searches submitted to the 33nd International Cosmic Ray Conference (Rio de Janeiro 2013) by the IceCube Collaboration.